Optimisation of Scores Generated by an Online Feline Health–Related Quality of Life (HRQL) Instrument to Assist the Veterinary User Interpret Its Results - Davies, Vinny; Reid, Jacqueline; Scott, E. Marian (Frontiers in Veterinary Science, 2021)
Using methodology previously described for the dog health-related quality of life (HRQL) tool (VetMetrica™), the aim was to optimise the scores profile of a comparable feline online HRQL instrument for monitoring HRQL in cats, to assist in its interpretation. Measuring HRQL helps quantify the impact of disease and its treatment on well-being, aids clinical decision making and provides information in clinical trials. In Study1, using data collected from previous studies, scores generated for three domains of HRQL (Vitality, Comfort, Emotional Wellbeing) in healthy cats were normalised using standard statistical techniques of logit transformation and T-scores, such that the average healthy cat has a score of 50 in all three HRQL domains. Using normalised scores from healthy and sick cats, a threshold score of 44.8 was determined, above which 70% of healthy cats should score. Study 2 determined the Minimal Important Difference (MID) in normalised score that constituted a clinically significant improvement in each domain. Three methods were tested in order to determine the MID, with the final choice made based on statistical and clinical considerations. Thresholds of 5, 7.5 and 5 were chosen for the three HRQL domains representing Vitality, Comfort and Emotional Wellbeing respectively. This study makes available a means of displaying HRQL scores from an online application in an easily interpretable manner and quantifies a clinically meaningful improvement in score. To illustrate the practical application of these developments, three case examples are presented. Example 1 illustrates the raw and normalised scores for a group of overweight cats enrolled in a Feline Weight Management Programme. Example 2 shows 3 groups of osteoarthritic cats, each with different severity of disease. The third is an elderly, unwell cat whose HRQL was recorded over time, specifically to facilitate end of life discussion between owner and veterinary clinician.